2020
DOI: 10.3390/su12020584
|View full text |Cite
|
Sign up to set email alerts
|

To Be Happy: A Case Study of Entrepreneurial Motivation and Entrepreneurial Process from the Perspective of Positive Psychology

Abstract: The pursuit of wealth maximization is considered to be the greatest driving force of entrepreneurship. However, this economic rational perspective cannot sufficiently answer why potential or continuous entrepreneurs still choose entrepreneurship or even continuous entrepreneurship in the face of high failure rate and tremendous uncertainty. On the basis of the dynamic process of entrepreneurship and the perspective of positive psychology, this study attempts to interpret the sustained motivation mechanism of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 54 publications
1
52
1
2
Order By: Relevance
“…The study of Mahadea and Ramroop (2015) also found that, on average, happier people tended to be educated, married with children, and treated fairly at work. But having too many children produced reduced individual happiness, On the other hand, other studies that seek to understand the entrepreneurial process and its relationship with happiness, such as those by Su et al (2020), have found findings where entrepreneurs in the process of establishing a company can persist in an uncertain environment, acquiring positive emotions. That is to say, the motivation for the sustainability of entrepreneurship originates from both the emotion of happiness and satisfaction from the very act of undertaking the entrepreneurship process, and emotional return is a performance dimension parallel to economic profitability.…”
Section: Entrepreneurship and Happinessmentioning
confidence: 98%
“…The study of Mahadea and Ramroop (2015) also found that, on average, happier people tended to be educated, married with children, and treated fairly at work. But having too many children produced reduced individual happiness, On the other hand, other studies that seek to understand the entrepreneurial process and its relationship with happiness, such as those by Su et al (2020), have found findings where entrepreneurs in the process of establishing a company can persist in an uncertain environment, acquiring positive emotions. That is to say, the motivation for the sustainability of entrepreneurship originates from both the emotion of happiness and satisfaction from the very act of undertaking the entrepreneurship process, and emotional return is a performance dimension parallel to economic profitability.…”
Section: Entrepreneurship and Happinessmentioning
confidence: 98%
“…As the research goes deeper, more researchers have noted other aspects of entrepreneurial motivation, analyzing how various factors affect entrepreneurial motivation from psychology. Su et al (2020) investigated the information in the social accounts of six entrepreneurs and explored the interaction between positive emotions and entrepreneurial motivation. Results suggested that positive emotions could affect entrepreneurial motivation and entrepreneurial process of entrepreneurs significantly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…the perceived net desire of entrepreneurs (NDSE), perceived self-efficacy (SE), and tolerance for risk (TR). Su et al (2020) explores the interaction between positive emotions and entrepreneurial motivation. The results showed that positive emotions significantly affect on entrepreneurship motivation and the entrepreneurial process of entrepreneurs.…”
Section: Literature Reviewmentioning
confidence: 99%